2018
DOI: 10.1073/pnas.1808168115
|View full text |Cite
|
Sign up to set email alerts
|

l -Serine–modified polyamidoamine dendrimer as a highly potent renal targeting drug carrier

Abstract: Effective delivery of drug carriers selectively to the kidney is challenging because of their uptake by the reticuloendothelial system in the liver and spleen, which limits effective treatment of kidney diseases and results in side effects. To address this issue, we synthesized L-serine (Ser)-modified polyamidoamine dendrimer (PAMAM) as a potent renal targeting drug carrier. Approximately 82% of the dose was accumulated in the kidney at 3 h after i.v. injection of 111 In-labeled Ser-PAMAM in mice, while i.v. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…Ser-PAMAM-Cys was synthesized by reacting Ser and Cys with third-generation (G3) PAMAM according to the HBTU-HOBt method [14]. Briefly, PAMAM dendrimer (86.5 mg, 0.013 mmol) was coupled with 0.22 eq (equivalent to the dendrimer surface amino group) Boc-Cys(Trt)-OH (40.9 mg, 0.088 mmol) and 0.88 eq Boc-Ser( t Bt)-OH (92.1 mg, 0.35 mmol) in DMF/DMSO (1:1) by mixing it with 1.1 eq HBTU (167 mg, 0.44 mmol), 1.1 eq HOBt (59.6 mg, 0.44 mmol), and 2.2 eq DIPEA(154 µL, 0.88 mmol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ser-PAMAM-Cys was synthesized by reacting Ser and Cys with third-generation (G3) PAMAM according to the HBTU-HOBt method [14]. Briefly, PAMAM dendrimer (86.5 mg, 0.013 mmol) was coupled with 0.22 eq (equivalent to the dendrimer surface amino group) Boc-Cys(Trt)-OH (40.9 mg, 0.088 mmol) and 0.88 eq Boc-Ser( t Bt)-OH (92.1 mg, 0.35 mmol) in DMF/DMSO (1:1) by mixing it with 1.1 eq HBTU (167 mg, 0.44 mmol), 1.1 eq HOBt (59.6 mg, 0.44 mmol), and 2.2 eq DIPEA(154 µL, 0.88 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…We recently developed the l -serine (Ser)-modified polyamidoamine (PAMAM) dendrimer. It is a highly potent renal-targeting drug carrier [14]. In mice, ~82% of the intravenously administered Ser-PAMAM dose accumulated in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modification of macromolecules is used to generate materials with fascinating physiochemical and biochemical properties for biomedical applications. l -Serine is a potent renal tubule–targeted modifier ( 20 ), which is also a potential targeting agent for kidney injury molecule–1 (Kim-1). Kim-1 is a transmembrane protein markedly up-regulated in injured kidneys, particularly renal proximal tubules, which induces the internalization and, therefore, the clearance of dead cells through the recognition of phosphatidylserine and oxidized lipoprotein on the surfaces of the dead cells ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Matsuura et al. modified PAMAM dendrimers with l-cysteine and l-serine and achieved dominant renal distribution in a renal ischemia/reperfusion injury animal model (Matsuura et al., 2018a , 2018b ). Their studies first confirmed that PAMAM dendrimers efficiently scavenge ROS and prevent renal ischemia/reperfusion injury.…”
Section: Formulation Approaches For Acute Pancreatitismentioning
confidence: 99%